Time-dependent behaviour of fully and partially penetrated geosynthetic encased stone columns. Issue 1 (12th July 2016) - Rajesh, S.
Abstract : This paper presents the results of a numerical investigation performed to examine the time-dependent behaviour of fully and partially penetrated geosynthetic encased stone columns (GESC). The investigation studied the influence of geosynthetic encasement, the stiffness of the encasement and the length of the column on the deformation behaviour of GESC. The influence of these factors is compared and rated in terms of the efficiency of the system. Results indicate a greater reduction in the settlement, lateral displacement and time taken for dissipation of excess pore water pressure when the stone column was encased with a geosynthetic material. The effective stress concentration ratio (the ratio of the effective vertical stress on the column to that on surrounding soft clay, ESCR) of the stone column was observed to increase up to a particular consolidation period, beyond which this ratio decreases drastically. Interestingly, when the stone column was encased with a geosynthetic material, the ESCR was found to increase during the entire period of consolidation and the value was much higher than for an ordinary stone column (OSC). A higher value of ESCR indicates less load being transferred from the column to the surrounding soft clay layer, hence better performance. With an increase in the geosynthetic stiffness from 500 to 5000 kN/m, the efficiency of GESC over OSC, considering load transfer from the column to the surrounding clay, increases from 1.03 to 4.63. For partially penetrated GESC, a reduction in the length of GESC decreases the ESCR drastically.